Read at home to do well at school: informal reading predicts achievement and motivation in English as a foreign language - Meyer, Jennifer; Fleckenstein, Johanna; Krüger, Maleika; Keller, Stefan Daniel; Hübner, Nicolas (Frontiers in Psychology, 2024)
This study explores the role of informal English language engagement for students' reading and listening skills, as well as their motivation to learn English. In an era of global interconnectedness, informal learning gains importance as a supplement to formal education.While a lot of prior research predominantly focused on college-level students and cross-sectional data, this study extends the evidence base with a large-scale longitudinal investigation involving secondary school learners (N = 1,994) in Germany. By analyzing extramural reading and listening activities, we add to the evidence that frequent informal reading significantly enhances students' English comprehension skills and fosters their motivation for language learning. This reaffirms previous cross-sectional findings and highlights the relevance of informal language activities. Additionally, discrepancies between reading and listening outcomes are discussed, shedding light on potential underlying factors. The outcomes underscore the significance of informal English engagement for effective language acquisition and fostering motivation.